Structural Strength Simulation of an Archimedes Screw Turbine Casing for MicroHydropower Applications - suherman Suherman; Tri Imam Sugatra; Ahmad Yunus Nasution (Talenta Publisher, 2026)
The Archimedes screw turbine (AST) has emerged as a promising technology for low-head micro-hydropower generation due to its simple configuration, high operational efficiency, and environmental compatibility. Nevertheless, studies addressing the structural performance and mechanical reliability of AST casing systems remain limited, particularly under different static loading conditions. This study aims to evaluate the structural strength of an ASTM A36 steel casing for an Archimedes screw turbine using finite element analysis in SolidWorks 2020. The novelty of this research lies in the integrated structural assessment of a closed-type AST casing, analysing stress distribution, strain behaviour, displacement characteristics, and factor of safety under various loading conditions prior to practical implementation. Static loads of 55.154 N, 57.704 N, and 84.584 N were applied to the casing structure. The simulation results revealed that the maximum von Mises stress increased from 7.517 × 10⁶ N/m² to 1.152 × 10⁷ N/m² as the load increased, while the maximum displacement rose from 1.050 × 10⁻¹ mm to 1.612 × 10⁻¹ mm. In contrast, the factor of safety decreased from 33.26 to 21.70, although all obtained values remained below the yield strength limit of ASTM A36 steel. The highest stress and strain concentrations were identified near the casing support and end sections, indicating critical regions requiring structural attention. Overall, the proposed casing design demonstrates satisfactory mechanical performance and structural safety for low-head micro-hydropower applications employing Archimedes screw turbines.